2003
DOI: 10.1596/1813-9450-3165
|View full text |Cite
|
Sign up to set email alerts
|

Social Protection in a Crisis: Argentina’s Plan Jefes y Jefas

Abstract: The article assesses the impact of Argentina's main social policy response to the severe economic crisis of 2002. The program was intended to provide direct income support for families with dependents and whose head had become unemployed because of the crisis. Counterfactual comparisons are based on a matched subset of applicants not yet receiving program assistance. Panel data spanning the crisis are also used. The program reduced aggregate unemployment, though it attracted as many people into the workforce f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 4 publications
1
77
0
5
Order By: Relevance
“…Available empirical literature on this method falls mainly into two groups; one has compared program and comparison groups where the program was in the pipeline (Chase, 2002;Galasso and Ravallion, 2004), the other has compared program and comparison groups where the program has not been placed at the time of survey (Amin et al, 1996;Hadi, 2002). The model can be written as follows…”
Section: (B) Methodsmentioning
confidence: 99%
“…Available empirical literature on this method falls mainly into two groups; one has compared program and comparison groups where the program was in the pipeline (Chase, 2002;Galasso and Ravallion, 2004), the other has compared program and comparison groups where the program has not been placed at the time of survey (Amin et al, 1996;Hadi, 2002). The model can be written as follows…”
Section: (B) Methodsmentioning
confidence: 99%
“…In Argentina, the Jefes programme was less well targeted than its Trabajar predecessor, but even here 40 percent of participants came from the poorest income quintile and 90 percent came from the poorest three quintiles. Galasso and Ravallion (2004) found that the Jefes programme was better targeted than other social programmes in Argentina. The unemployment rate was reduced by approximately 2.5 percentage points (but the effect on poverty was larger, as the participation rate rose by about the same amount, as women with dependents who had not been in the labour force joined the programme).…”
Section: Experiences With Employment Guarantees and Social Assistancementioning
confidence: 97%
“…The new programme provided cash to unemployed household heads with dependent children or disabled adults. Participants were supposed to work for 20 hours per week on socially useful projects (Galasso and Ravallion, 2004). Botswana introduced a cash-for-work programme in 1992-93, providing 7 million person-days of employment (in a country with a tiny population) (Subbarao, 2001).…”
Section: Experiences With Employment Guarantees and Social Assistancementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, expanding the survey to the whole country might itself lead to some errors. Nonetheless, some authors such as Galasso and Ravallion (2004) have employed the same source of information to assess the Unemployed Heads of Household Plan, also in a context of beneficiary number underestimation.…”
Section: Argentina: Impacts Of the Child Allowance Programme On The Lmentioning
confidence: 99%